Human neurodegenerative disease: insights from Drosophila genetics - Bonini, Nancy (Henry Stewart Talks, 2008)
The fly as a model for human disease, Modelling human polyglutamine disease, Molecular chaperones as modifiers of polyglutamine disease using the fly, Importance and impact of disease protein function for effects of the toxic mutant protein, Insights from the fly on the mutational basis of disease, in instability of the trinucleotide repeat expansion
Reviewed at 2018/05/31